Seismic reservoir characterization of deep carbonates under complex overburden: a lithofacies-association zonation workflow, Longwangmiao Formation, Sichuan Basin - Lei Tan; Yuanzhi Zhou; Junliang Li; Linzhi Zhang; Ya Zhang; Pingchao Fang; Minzhi Zhang; Bowen Liu; Longyan Yin; Lin Qiao; Mingzhi Kuang; Hong Liu (Carbonates and Evaporites, 2026)

Isolation and characterization of two novel species Neorhizobium fuzhouense sp. nov. and Neotabrizicola paludis sp. nov - Shu-Yi Zhang; Xie-Feng Lu; Peng Gao; Ling Yao; Hui-Yuan Jiang; Guo-Hong Liu; Shun-Gui Zhou (Antonie van Leeuwenhoek, 2026)

Biocontrol for Shrimp Disease: Comprehensive Review and a Bacterial Disease Biocontrol Practice - Xinyi He; Jian He; Minghong Liu; Menghuang Xu; Jianjun Jiang; Minze Liao; Chengcheng Wu; Peiyun Han; Long Zhang; Shaoping Weng; Zhixun Guo; Jianguo He (Reviews in Aquaculture, 2026)
Biocontrol is a key strategy for disease control, as it is environmentally friendly and widely applicable. This review elaborates on biocontrol in aquaculture, particularly in shrimp culture. Biocontrol in shrimp culture mainly relies on four strategies: (i) direct kill pathogen by Bdellovibrio or bacteriophages; (ii) suppression of intestinal pathogens with probiotics; (iii) reduction of environmental pathogens via probiotics, biofloc, or bivalves and fish; and (iv) blocking transmission of pathogens using predatory fish. “Shrimp‐fish polyculture” system for diseased biocontrol, which is convenient, effective, and affordable, focuses on blocking disease transmission routes. The efficacy of this strategy has been firmly established for white spot syndrome virus (WSSV). However, its application to other shrimp diseases is not widespread. Herein, a “shrimp‐fish polyculture” biocontrol plan was designed and successfully validated against Vibrio harveyi in shrimp. These findings successfully expand the application of the “shrimp‐fish polyculture” system to the control of bacterial diseases in shrimp, thereby offering new perspectives and methods for the biocontrol of diseases caused by various shrimp pathogens.

Higher density of earthworms (Pheretima guillelmi) enhances soil carbon sequestration and carbon pool management index in a subtropical forest - Yufeng Qiu; Yue Zhuang; Tanja Trakić; Ronggui Tang; Yihong Liu; Youchao Chen; Xie Wang; Yanjiang Cai; Scott X. Chang (Applied Soil Ecology, 2026)

Endophyte-derived synthetic microbial communities for sustainable agricultural practices: Enhancing crop productivity and disease suppression in pepper - Kaiheng Lu; Leigang Zhang; Jiahui Zhou; Qiuling Li; Xiangyang Yu; Changhong Liu (Applied Soil Ecology, 2026)

Distribution and health risk assessment of heavy metals in the soil and tea of the Yangai tea farm - Yun Huang; Haijie Song; Rou Wang; Jing Shi; Jianhong Liu; Yishu Peng; Tao Jin; Jianjun Liu (Applied Soil Ecology, 2026)

Impact of bacteriocins on multidrug‐resistant bacteria and their application in aquaculture disease prevention and control - Xiaoli Chen; Hong Liu; Shuangping Liu; Jian Mao (Reviews in Aquaculture, 2024)
Aquaculture plays an important role in meeting human demand for animal protein. Disease is a critical factor that restricts the green and healthy development of aquaculture. Intensive aquaculture practices can increase the susceptibility of aquatic animals to pathogens due to environmental stress. Antibiotics are commonly used for disease prevention and control, but their frequent use in aquaculture can increase the risk of antibiotic‐resistant bacteria and resistance gene transmission, posing a threat to the health of aquatic animals and humans. Recent studies have shown that bacteriocins have inhibitory effects on different species of bacteria, fungi and viruses, and can even affect natural resistance structures such as bacterial biofilms, presenting promising prospects as antimicrobial agents. Bacteriocins have potential applications in various fields such as agriculture, food and medicine, but limited research has been conducted on their impact on aquaculture disease prevention and control, and the underlying mechanisms remain to be explored. Therefore, this review aims to summarise the classification, sources, preparation methods, antibacterial activity against multidrug‐resistant bacteria and application of bacteriocins as antimicrobial agents in aquaculture disease prevention and control. In addition, limitations of bacteriocin application in aquaculture and future research directions are also discussed.

Offshore aquaculture in China - Lina Long; Huang Liu; Mingchao Cui; Chenglin Zhang; Chong Liu (Reviews in Aquaculture, 2024)
The mariculture industry is planning to move offshore due to the decline of China's inshore fishery resources, the deterioration of the water environment, inefficient industrial structure and other influencing factors. This article first analyses the imbalance between supply and demand of aquatic products, the development space of offshore aquaculture and the supporting policies, thereby concluding that China has significant potential to develop offshore aquaculture. Subsequently, the development status of offshore aquaculture in China is examined. The research progress of China's offshore aquaculture facilities, marine hydrology, environmental carrying capacity, aquaculture technology and the status of aquaculture operation equipment are also summarized. Furthermore, the problems existing in the development of offshore aquaculture are pointed out. On this basis, future development ideas for China's offshore aquaculture can be planned in terms of sea area layout, optimized and improved seed production systems, and research and development of offshore aquaculture technology and pellet feed. The relationship between the development of offshore aquaculture and ecological protection should be coordinated. Additionally, an energy security system can be built based on clean energy, and the development of related industries can be driven through the complementary industrial division of labour. The present work aims to provide a reference for promoting the development of offshore aquaculture in China.

Advances of intra‐species molecular typing analysis of aquatic probiotics approved by the Chinese Ministry of Agriculture - Juan Hu; Yuanyuan Yao; Yalin Yang; Chenchen Gao; Fengli Zhang; Rui Xia; Chao Ran; Zhen Zhang; Jihong Liu Clarke; Zhigang Zhou (Reviews in Aquaculture, 2021)
Probiotics confer a health benefit on the host and could be used as a good alternative to antibiotics. Probiotics are strain‐specific when exerting their function, so it is necessary to identify them to strain level. In recent years, intra‐species molecular typing and identification methods have developed rapidly, which commonly are used for typing the main pathogenic bacteria and rare for studies on probiotic typing, whilst it is imperative. This article describes molecular typing methods including AFLP, RAPD, PFGE, ribotyping, MLST, rep‐PCR and whole‐genome sequencing to identity some aquatic probiotics approved by the Ministry of Agriculture of China, which are Bifidobacterium , Enterococcus , Lactobacillus , Pediococcus , Aspergillus , Bacillus , Rhodopseudomonas palustris and Streptococcus thermophilus . In addition, the principles, applications, advantages and disadvantages of these typing methods are also discussed.

Surface display system for probiotics and its application in aquaculture - Yuan‐Yuan Yao; Ya‐Lin Yang; Chen‐Chen Gao; Feng‐Li Zhang; Rui Xia; Dong Li; Juan Hu; Chao Ran; Zhen Zhang; Jihong Liu‐Clarke; Zhi‐Gang Zhou (Reviews in Aquaculture, 2020)
Aquaculture is a fast‐growing and rapidly expanding industry in the world. Probiotics are widely used in aquaculture and have provided benefits to aquatic animal health, and it is also a promising alternative to antibiotics for control of fish diseases. With the development of biotechnology, new expression systems and novel techniques for the surface display of heterologous proteins in surface of probiotics cells have been developed. This review provides an overview of the systems and strategies for displaying functional proteins on the surface of probiotics commonly used in aquaculture, which are Bacillus subtilis , Bacillus thuringiensis , lactic acid bacteria represented by Lactococcus lactis and yeast. Their applications in aquaculture especially for oral vaccine development afforded by this technology and prospects and challenges associated with this technology are also highlighted.